2019
DOI: 10.1016/j.aller.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Contact sensitization in children with atopic dermatitis

Abstract: Cutaneous sensitization can develop in children with atopic dermatitis, therefore allergic contact dermatitis should be kept in mind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
8
1
3
Order By: Relevance
“…The most prevalent allergens in AT patients were found to be nickel sulphate, fragrance mix (I) 8%, balsam of Peru, thiomersal, and cobalt chloride. This finding was in agreement with previous studies which reported that nickel sulphate was also the most prevalent allergen in patient cohorts [ 38 40 ]. Similar results have been also previously reported for fragrance mix [ 41 43 ], balsam of Peru [ 44 47 ], thiomersal [ 48 ], and cobalt chloride [ 44 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 94%
“…The most prevalent allergens in AT patients were found to be nickel sulphate, fragrance mix (I) 8%, balsam of Peru, thiomersal, and cobalt chloride. This finding was in agreement with previous studies which reported that nickel sulphate was also the most prevalent allergen in patient cohorts [ 38 40 ]. Similar results have been also previously reported for fragrance mix [ 41 43 ], balsam of Peru [ 44 47 ], thiomersal [ 48 ], and cobalt chloride [ 44 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 94%
“…Frequent use of emollients and topical medications were also recognized as a significant clinical problem in both children and adults with AD [35][36][37], including methylchloroisothiazolinone (wet wipes! ), cocamidopropyl betaine and wool alcohols (lanolin, Amerchol L-101), and fragrances [33,38,39]. These are also chemicals for which irritant patch test reactions are possible though.…”
Section: Allergic Contact Dermatitis and Atopymentioning
confidence: 99%
“…Лікування алергодерматозів передбачає: дотримання режиму дня та дієти, контроль за довкіллям щодо елімінації алергенних та неалергенних факторів, лікувально косметич ний догляд за шкірою, фармакотерапія систем на і місцева, фототерапія, фізіотерапія, лікуван ня супутніх захворювань, навчання пацієнтів, реабілітація і профілактика загострень [2,4,5,10,12].…”
Section: он мочульская тм косовскаяunclassified
“…Мембраностабілізуючі засоби, кротони (кромоглікат натрію, недокромил натрію) антимедіаторні препарати широкого спектра дії, які досить часто використовуються в ліку ванні алергодерматозів. Кромони стабілізують мембрани опасистих клітин і гальмують надхо дження іонів кальцію до клітин, унаслідок чого блокується розвиток алергічної реакції, зумо вленої взаємодією антитіла з антигеном, а також усувають гемокоагуляційні порушення та порушення мікроциркуляції [1,2,8,9,12]. Мембраностабілізуючі препарати признача ються як у комплексі з основними методами лікування, так і як профілактичне лікування в реабілітаційному періоді на тривалий термін протягом кількох тижнів і навіть місяців [2,4,10].…”
Section: он мочульская тм косовскаяunclassified
See 1 more Smart Citation